STUDI KASUS TENTANG PELAKSANAAN PEMBELAJARAN BATIK DI KELAS XII SEKOLAH MENENGAH KEJURUAN NEGERI 8 PADANG - ZIZKA AYU LIDYA, Dra. Zubaidah, M.Pd., Drs. Erwin, M.Sn. (Universitas Negeri Padang, 2019)
This study aims to see the implementation of batik learning in class XII of SMK N 8 Padang. This study uses a qualitative approach with descriptive methods. Batik learning at SMK N 8 Padang has students who are contestants in the field of batik. This is because the teacher delivers the material with varied methods, the teacher also uses media that can be seen and observed by students such as student focus and batik products. So that students do not get bored in attending the lesson. In addition, the teacher provides motivations that are able to provoke students to take part in learning and work in the field of batik. In practical learning the teacherparticipates in practicing how to batik properly, so students are not confused and all students can see firsthand how to do the assignments given by the teacher. Besides batik learning at SMK N 8 Padang using teaching vectory model, namely the implementation of partner industry systems in existing production units in SMK, this school already has its own batik products under the UBA brand namely batik works made by students of SMK N 8 Padang. Within a week students learn theory and the following week students learn to make batik on cloth measuring 2 meters for each student. So in a week students are able to complete one batik task measuring 2 meters. Based on this, it can be seen that the teacher carries out maximum learning of batik.Keywords: Learning Implementation, Batik Learning.